Towards item matching task: systematic review - Cherednichenko, Olga; Ivashchenko, Oksana; Kirchmayer, Jozef (Bratislava University of Economics and Management, 2023)
With the rapid growth of e-commerce, the challenge of item matching has become increasingly significant. This research focuses on exploring contemporary approaches to entity resolution and their potential benefits in improving product matching. A comprehensive framework for conducting a literature review is proposed, enabling the classification of references and the selection of relevant approaches. The research aims to answer key questions regarding existing techniques, their strengths and limitations, their effective application in e-commerce, and the gold standard in entity resolution. The paper provides an overview of the research task, describes the methodology and sources utilized, presents the golden standard in entity resolution, and introduces a proposed framework for literature review.
Keywords: digitalization; e-commerce; entity resolution; item matching; systematic review